Capitalist expansion and the decline of common property ecosystems in China, Vietnam and India - Sugden, Fraser; Punch, S. (Wiley, 2014)
This article identifies some of the multiple processes of capitalist development through which access to common property resources and their utility for communities are undermined. Three sites in upland Asia demonstrate how patterns of exclusion are mediated by the unique and selective trajectories through which capital expands, resulting in a decline of common property ecosystems. The process is mediated by economic stress, ecological degradation and political processes such as state-sanctioned enclosure. The first case study from Shaoguan, South China, indicates how rapid capitalist industrialization has depleted the aquatic resource base, undermining the livelihoods of fishing households yet to be absorbed into the urban working class. At the second site, in Phu Yen, Vietnam, capitalist development is limited. However, indirect articulations between capitalism on the lowlands and the peasant economy of the uplands is driving the commercialization of agriculture and fishing and undermining the utility of communal river and lake ecosystems. In the third site, Buxa in West Bengal, India, there is only selective capitalist development, but patterns of resource extraction established during the colonial period and contemporary neoliberal ‘conservation’ agendas have directly excluded communities from forest resources. Restrictions on access oblige them to contribute subsidized labour to local enterprises. The article thus shows how communities which are differentially integrated into the global economy are excluded from natural resources through complex means.